Comparison of Pregnancy and Neonatal Outcomes in HELLP Syndrome and Preeclampsia - Z Bouzari, (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: HELLP syndrome is a serious presentation of pre-eclampsia and eclampsia during pregnancy and its diagnosis is difficult because of lack of specific features. This syndrome is associated with prenatal and neonatal morbidity and mortality. The aim of the present study was to compare the maternal and neonatal outcomes of HELLP syndrome with preeclampsia in Yahyanejad hospital (Babol, Iran) in the past ten years.METHODS: This cross-sectional study was performed on all patients with pre-eclampcia/eclampcia who were hospitalized in Yahyanejad hospital during 10 years. Primary data, clinical and laboratory data, prenatal and maternal complications included (cesarean section, placental abruption, need to blood transfusion, liver hematoma, pulmonary edema, acute renal failure, DIC, brain hematoma and infection, intra-abdominal hemorrhage, ARDS and maternal mortality) and neonatal complications included (preterm neonates, IUGR, NICU admission and neonate mortality) were compared.FINDINGS: In this study, from 445 patients who were evaluated, 361 patients (81.3%) with mild preeclampsia, 83 patients (18.7%) with severe pre eclampsia and 1 (%0.2) with eclampsia were hospitalized in primary diagnosis, that 12 patients (2.7%) had HELLP syndrome symptoms. Cases of placental abruption, liver hematoma, pulmonary edema, need to blood transfusion, acute renal failure, DIC and maternal mortality in patients with HELLP syndrome was significant in compared to preeclampsia (p<0.05). Neonatal complications included preterm neonates, IUGR, NICU admission in patients with HELLP syndrome were significant in compared to preeclampsia (p<0.05). Also no case of brain hemorrhage and infection, ARDS, intra-abdominal hemorrhage, IUFD and neonatal mortality was reported.CONCLUSION: According to the results of this study, maternal and fetal complications in patients with HELLP syndrome can be prevented and this could be result of early diagnosis and appropriate management.